Prognosis of Urinary Bladder TCC in Young Adults: A Single Center Experience (Global Journal of Medical Research, 2018)
Abstract not found
Keywords: TCC urinary bladder; recurrence; progression; grade; multifocality; smoking; recurrence- free survival; progression- free survival